FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN PENERAPAN AKUNTANSI BERBASIS AKRUAL PADA PEMERINTAH KABUPATEN LOMBOK BARAT - - Budiarto (SOLID, 2018)
This study is intended to determine the factors that influence the success of local governments in the implementation of PP 71/2010 on Accrual Based Government Accounting Standard. This quantitative research employs the regression method to analyse the regulations, human resources, commitment, other supporting elements and training which seem to influence the accomplishment of local governments in the implementation of PP 71/2010 on Accrual Based Government Accounting Standard. The population of the study is the regional finance management personnel in 32 Government Work Units (SKPD) within the district government of West Lombok comprising of head of SKPD and/or the finance administration officer (PPK), treasurer, and the planning staff. Sample is selected through the purposive sampling technique in which 96 respondents are given questionnaires. Only 71 respondents return the questionnaires. Likert scale is used for the data measurement.The result of the study shows that regulation, human resources, commitment, other supporting, and training elements partially and simultaneously have positive effect to the accomplishment of local governments in the implementation of PP 71/2010 on Accrual Based Government Accounting Standard.Keywords:  Accrual Basis, regulation, human resources, commitment, supporting elements, training